2017
DOI: 10.1007/s00384-017-2935-0
|View full text |Cite
|
Sign up to set email alerts
|

Can the combination of laparoscopy and enhanced recovery improve long-term survival after elective colorectal cancer surgery?

Abstract: The use of a laparoscopic approach with enhanced recovery after surgery management appears to have long-term survival benefits following colorectal cancer resection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 12 publications
0
19
0
Order By: Relevance
“…After adjustment for BMI, tumour location and neoadjuvant treatment, compliance may have been associated with a reduction in 5‐year cancer‐specific mortality. Others have reported better OS for patients undergoing laparoscopic surgery within an ERP.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…After adjustment for BMI, tumour location and neoadjuvant treatment, compliance may have been associated with a reduction in 5‐year cancer‐specific mortality. Others have reported better OS for patients undergoing laparoscopic surgery within an ERP.…”
Section: Discussionmentioning
confidence: 96%
“…Given the advantages of ERPs and MIS, a combination of both may potentiate improvements in cancer‐related outcomes. One recent study within an enhanced recovery framework demonstrated improved oncological results in MIS surgery, and other authors have described a correlation between ERP compliance and improved 5‐year oncological outcomes. Both series used robust follow‐up data, but these were aggregated from heterogeneous patient populations, which featured colonic and rectal cancers treated with both open and minimally invasive techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Of these 26 articles, 3 were randomized trials [ 12 , 13 , 15 ], which were evaluated by Jadad score, and the other 23 were prospective or retrospective cohort studies, which were evaluated by the NOS. Eighteen articles compared conventional care with ERAS [ 10 21 , 29 – 34 ], 7 studies compared high adherence to ERAS with low adherence [ 16 , 22 26 , 34 ], and 4 studies [ 27 29 , 35 ] investigated the outcome of one single item altered within ERAS protocol. The elements of the ERAS protocol in each article are presented in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
“…The pathogenesis of colorectal cancer still remains unknown as there are numerous pathogenic factors, which makes the treatment of colorectal cancer more difficult ( 5 7 ). Surgical resection has been the radical treatment for colorectal cancer; however, the probability of infection after surgery is high, resulting in poor survival rate of patients ( 8 , 9 ). Therefore, the relevant mechanisms of colorectal cancer need to be clarified and new potential therapeutic targets should be investigated to improve the prognosis of patients with colorectal cancer.…”
Section: Introductionmentioning
confidence: 99%